Perbandingan Saturasi Oksigen pada Perokok dan Bukan Perokok di Dataran Tinggi Tomohon dan Dataran Rendah Manado - Polii, Thalia R.; Rumampuk, Jimmy; Lintong, Fransiska (e-Biomedik, 2017)
Abstract: Cigarette smoking has many negative impacts to human body inter alia declined oxygen saturation due to binding of CO to Hb. Aside from smoking, declined barometric pressure on higher surface can also decrease the oxygen saturation. This study was aimed to understand the comparison of oxygen saturation between smokers and non-smokers in highland of Tomohon and lowland of Manado. This was an analytical study with a cross-sectional design. There were 60 subjects, smokers and non-smokers, from highland and lowland. The results showed that there was a significant difference in mean oxygen saturation between smokers of highland and of lowland (P=0.002) but there was no significant difference in mean oxygen saturation between non-smokers of highland and of lowland (P=0.0255). There was a significant difference in mean oxygen saturation between smokers of highland and non-smokers of lowland (P=0.001) but there was no significant difference in mean oxygen saturation between non-smokers of highland and smokers of lowland (P=0.424). There was a significant difference in mean oxygen saturation between smokers and non-smokers of highland (P=0.010) but there was no significant difference in oxygen saturation between smokers of highland and non-smokers of lowland (P=0.714). Conclusion: There were significant differences in oxygen saturation between smokers of highland and of lowland; smokers of highland and non-smokers of lowland; as well as smokers and non-smokers of highland. On the other hand, there were no significant differences in oxygen saturation between non-smokers of highland and of lowland; non-smokers of highland and smokers of lowland; as well as smokers and non-smokers of lowland.Keywords: oxygen saturation, smokers, non-smokers, highland, lowlandÂ Abstrak: Rokok memiliki dampak buruk pada kesehatan manusia, salah satunya ialah menurunnya saturasi oksigen akibat ikatan yang terjadi antara CO dengan Hb. Selain merokok, penurunan tekanan barometrik pada ketinggian juga dapat menurunkan kadar saturasi oksigen dalam darah. Penelitian ini bertujuan untuk mengetahui perbedaan saturasi oksigen pada perokok dan bukan perokok di dataran tinggi Tomohon dan di dataran rendah Manado. Jenis penelitian ialah analitik dengan desain potong lintang. Subyek penelitian berjumlah 60 orang yang terdiri dari perokok dan bukan perokok di dataran tinggi dan rendah. Hasil penelitian mendapatkan perbedaan rerata saturasi oksigen yang bermakna antara perokok dataran tinggi dan perokok dataran rendah (P=0,002). Tidak terdapat perbedaan rerata saturasi oksigen yang bermakna antara bukan perokok dataran tinggi dan bukan perokok dataran rendah (P= 0,255). Terdapat perbedaan rerata saturasi oksigen yang bermakna antara perokok dataran tinggi dan bukan perokok dataran rendah (P=0,001). Tidak terdapat perbedaan rerata saturasi oksigen yang bermakna antara bukan perokok dataran tinggi dan perokok dataran rendah (P=0,424). Terdapat perbedaan rerata saturasi oksigen yang bermakna antara perokok dan bukan perokok di dataran tinggi (P=0,010). Tidak terdapat perbedaan rerata saturasi oksigen yang bermakna antara perokok dan bukan perokok di dataran rendah (P= 0,714). Simpulan: Terdapat perbedaan rerata saturasi oksigen yang bermakna antara perokok dataran tinggi dan perokok dataran rendah; perokok dataran tinggi dan bukan perokok dataran rendah; serta perokok dan bukan perokok di dataran tinggi. Tidak terdapat perbedaan rerata saturasi oksigen yang bermakna antara bukan perokok dataran tinggi dan bukan perokok dataran rendah; bukan perokok dataran tinggi dan perokok dataran rendah; serta perokok dan bukan perokok di dataran rendah.Kata kunci: saturasi oksigen, perokok, bukan perokok, dataran tinggi, dataran rendah